(3EJMGa Phi GdGLJgGO HKeQGJ GdLgGOs
(3ChdgG (B:s
(3GdMeO ddg GdPi fTQ Ydi GdMGfbjf CYdGe YOdg hfKQ Ydi HSGW GdhLhO dCdF LhOg haVdg s
(3BNQgG (B:s
(3OYhGge ajgG SHMGfc Gddge hJMjJge ajgG SdGe hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf JeJ GdQSGdI HYhf Gddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs